Multi-objective Fuzzy Bi-matrix Game Model: A Multicriteria Non-Linear Programming Approach - Zhang, Wei; Xing, Yumei; Qiu, Dong (Symmetry (Basel), 2017)
A multi-objective bi-matrix game model based on fuzzy goals is established in this paper. It is shown that the equilibrium solution of such a game model problem can be translated into the optimal solution of a multi-objective, non-linear programming problem. Finally, the results of this paper are demonstrated through a numerical example.